Pengaruh Komitmen Organisasi dan Penerapan Good Corporate Governance Terhadap Kecenderungan Kecurangan Akuntansi - Antari, Ni Kadek Sri Tirta; Cokorda Gde Bayu Putra; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2025)
Fraud in financial institutions can be explained by the fraud triangle theory which emphasizes the factors of pressure, opportunity, and rationalization. The purpose of t.his studly was to determine the effect of organizational commitment and good corporate governance on the tendlency of accountiing firaud. Tlhis researcih was condiucted in Kerambitan District, Tabanan Regency, Bali on 26 LPDs in Kerambitan District. The po.pulation in this studly wer.e all LPD employees, totaling 132 people and by using the Slovin Formula, the sample members were determined to be 78 LPD employees. The sampling technique was carried out by purposive sampling. The instrumenlt test was cariried out by teslting the vallidity and reliabiility. The data analysiis techlnique used is multiplle liinear regresision using SPSS softw.are. The results of the analysis of determination show the effect of organizationall commitmient and good corporate governance on the tendency of accountiing frauid by 71.7%. Partial significance test proves that organizational commitment and good corporatte goveirnanice has a negative and significant effect on accounting tendencies.